Saprochaete clavata Invasive Infections – A New Threat to Hematological-Oncological Patients - Buchta, Vladimir; Bolehovská, Radka; Hovorková, Eva; Cornely, Oliver A.; Seidel, Danila; Žák, Pavel (Frontiers in Microbiology, 2019)
Background: Saprochaete clavata (Magnusiomyces clavatus) is a filamentous yeast-like fungus that has recently been described as a newly emerging pathogen mostly in patients with acute leukemia. The diagnosis of this mycosis is very difficult and an optimal treatment regimen has yet to be established. Methods: Retrospective study that includes cases of proven and probable S. clavata infection, including epidemiological data, which were diagnosed at the University Hospital, Hradec Kralove, Czech Republic between March 2005 and December 2017. Review of literature and FungiScope™database of documented cases of S. clavata infection. Results: Six cases (5 females, 1 male) of blood-stream S. clavata infections at the hemato-oncological department of a large hospital were described. Overall, 116 strains of S. clavata were isolated from clinical specimens of 54 patients; most of them belonged to the respiratory tract (60.3%). Saprochaete clavata was the most frequently recovered species among arthroconidial yeasts (Trichosporon, Galactomyces, Magnusiomyces) from the blood. All patients with S. clavata infection had profound neutropenia, a central venous catheter, broad-spectrum antibiotics and antifungal prophylaxis; four had a history of a biliary tract system disease. The diagnosis was based on a positive blood culture in all patients. Four patients died of multiorgan failure and sepsis despite treatment with lipid-based amphotericin B and/or voriconazole. Conclusions: Saprochaete clavata infection represents a new life-threatening mycosis in severely immunocompromised patients. The successful outcome of treatment seems to be critically dependent on the early diagnosis and the recovery of underlying conditions associated with immune dysfunction or deficiency.